2015
DOI: 10.1016/j.jneumeth.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Real time adenosine fluctuations detected with fast-scan cyclic voltammetry in the rat striatum and motor cortex

Abstract: Background Adenosine serves many functions within the CNS, including inhibitory and excitatory control of neurotransmission. The understanding of adenosine dynamics in the brain is of fundamental importance. The goal of the present study was to explore subsecond adenosine fluctuations in the rat brain in vivo. Method Long Evans rats were anesthetized and a carbon fiber electrode was positioned in the motor cortex or dorsal striatum. Real time electrochemical recordings were made at the carbon fiber electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Changes in extracellular adenosine concentrations have been observed on time scales ranging from minutes to hours. However, a faster form of transient adenosine release has recently been characterized, which lasts only a few seconds . While adenosine release can be electrically stimulated, recent studies have found transient adenosine events that are not stimulated, but spontaneous, and occur randomly. ,, Rapid adenosine can modulate electrically stimulated dopamine release . There is also a correlation between transient adenosine and transient oxygen events, supporting the hypothesis that rapid adenosine serves a neuroprotective role .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Changes in extracellular adenosine concentrations have been observed on time scales ranging from minutes to hours. However, a faster form of transient adenosine release has recently been characterized, which lasts only a few seconds . While adenosine release can be electrically stimulated, recent studies have found transient adenosine events that are not stimulated, but spontaneous, and occur randomly. ,, Rapid adenosine can modulate electrically stimulated dopamine release . There is also a correlation between transient adenosine and transient oxygen events, supporting the hypothesis that rapid adenosine serves a neuroprotective role .…”
Section: Introductionmentioning
confidence: 92%
“…11 While adenosine release can be electrically stimulated, 12 recent studies have found transient adenosine events that are not stimulated, but spontaneous, and occur randomly. 11,13,14 Rapid adenosine can modulate electrically-stimulated dopamine release. 15 There is also a correlation between transient adenosine and transient oxygen events, supporting the hypothesis that rapid adenosine serves a neuroprotective role.…”
Section: Introductionmentioning
confidence: 99%
“…177 Recently, the Budygin group also reported spontaneous adenosine release in rat striatum and motor cortex. 178 Although they used the same waveform, there is a discrepancy in the data as they did not observe a secondary oxidation peak. Their spontaneous transients were at much higher frequencies than previously reported, and they also detected adenosine efflux in response to a brief tail pinch.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Spontaneous adenosine transients were detected for the first time in vivo , with a characteristic electrochemical signature of a primary oxidation peak at +1.4 V and a second oxidation peak at +1.0 V in subsequent scans . Recently, the Budygin group also reported spontaneous adenosine release in rat striatum and motor cortex . Although they used the same waveform, there is a discrepancy in the data as they did not observe a secondary oxidation peak.…”
Section: Electrochemical Detection Of Neurotransmittersmentioning
confidence: 99%
“…Our lab has recently discovered a new mode of adenosine signaling: spontaneous, transient release that lasts for only about three seconds. 710 These spontaneous transients are modulated by A 1 receptors 7 and A 2a receptors 11 in the caudate and prefrontal cortex but regulation by other neurotransmitter receptors has not been studied.…”
Section: Introductionmentioning
confidence: 99%